Profil of Swamp Water Fish in Manter Village, Sintang Regency, West Borneo - Rizkiyani, Ainun; Afriani, Rachmi; Nazarudin, Nazarudin; Sri Sumarni, Sri Sumarni (JURNAL BIOLOGICA SAMUDRA, 2025)
This study aims to describe the profile of swamp fish resources based on community knowledge in Manter Village, Sintang Regency. The community’s understanding of the potential of local fish resources can be developed into village government policies to optimize the potential of local resources thereby supporting increased income and community welfare while promoting food self-sufficiency. This research employed interview and observation methods. Interviews were conducted with local community members to gather information on fish species found in swamp waters, while observations were carried out to determine the sampling points. Sampling points were determined using purposive sampling in four hamlets: Pandan Arum, Sidodadi, Purwosari, Simpang Manter. The results showed that there were 11 swamp fish species found in Manter Village, including Sepat Rawa (Trichogaster trichopterus), Sepat Mutiara (Trichopodus leeri), Cucut (Luciocephalus pulcer), Toman (Channa micropeltes), Gabus (Channa striata), Betok (Anabas tustudineus), Lele Lembat (Clarias nieuhifii), Seluang (Rasbora sp), Biawan (Helostoma temincki), Sili Batik (Mastacembulus armatus), dan Belut Rawa (Synbranchus bengalensis). The fish resources found in Manter Village are primarily utilized directly by the community for household consumption. These fish species can be further developed by the community through processed products to increase income and improve community welfare, ultimately contributing to achieving food-self sufficiency in Manter Village.